Clinical Features and Survival Outcome of Early-Stage Primary Pulmonary MALT Lymphoma After Surgical Treatment - Xu, Ye; Zheng, Min; Guo, Qingkui; Wang, Ning; Wang, Rui (Frontiers in Surgery, 2021)
Abstract: Background: We aim to study the clinical features and survival outcome of early-stage primary pulmonary MALT lymphoma underwent surgery. Methods: This is a retrospective, single-center study including 32 patients with early-stage primary pulmonary MALT lymphoma. Univariate and multivariate COX analysis were performed to select independent prognostic factors. The overall survival (OS), was analyzed by Kaplan-Meier method and compared with log-rank test. Results: Among the 32 patients included, there were 16 males (50.0%) and 16 females (50.0%). The average age was 59.2 years old. 10 patients had non-specific clinical symptoms including cough, expectoration and chest pain, 4 patients had B symptoms. CT images are not specific and can be shown as peripheral, central, solid, ground glass, but more peripheral (93.8%) and solid (75.0%). In prognostic analysis, univariate analysis showed that tumor stage and size were associated with RFS and OS (HR=1.105,95%CI:1.021-1.197,P=0.011 ;HR=1.211,95%CI:1.158-1.968,P=0.003,respectively). It’s seems to indicate that higher stage and larger size indicate a worse prognosis, but we could not find statistically significant predictors in multivariate analysis. Sublobectomy was performed in 21(65.6) cases, and Lobectomy was performed in the other 11(34.4) cases, both of them can achieve good prognosis (5-year RFS and OS are 100%), and there is no significant difference between them. Conclusions: The clinical manifestation of early-stage primary pulmonary MALT lymphoma is not significantly specific, and surgical resection is an effective treatment.